Quo vadis labor Justice in Cuba? Considerations in key of lege ferenda - Menoya Zayas, Sandys (2021)
The work reviews a recurrent topic in labor and social security law in Cuba: the administration of justice in the solution of conflicts. Its objective is to support a set of proposals that contribute to the improvement of the Cuban labor justice system, in line with international trends in the matter, and that preserves the principlesand features that define it. The research employed theoretical methods, such as historical-legal, legal-doctrinal, and exegetical-analytical; and empirical methods, such as document review. As a result of theanalysis of doctrine and legislation, the main problems and challenges facing labor justice in Cuba and, in general, labor and social security procedural law are identified, which made it possible to propose some guidelines required for its future improvement given a labor law reform.